Population of Waterbirds in Two Mangrove Types, Avicennia and Rhizophora in Iran - Ghasemi, Saber (2011)
Relationship between mangroves and their associated marine life cannot be overemphasized. Mangrove habitats play host to a moderate number of waterbirds around the globe, but their relative roles of mangrove habitat structure in association with variation in both individual waterbirds distributions and their communities have yet explicitly examined. The objectives of this study were: (1) To determine the abundance, diversity and evenness of waterbirds in two different type of mangroves habitat (Avicennia and Rhizophora), (2) To compare environmental variables, soil as well as surrounding water sources, and vegetation structure as effective components in determining the safe habitat for waterbirds, and (3) To examine the diversity and density of gastropod and mudskipper in two habitats as effective components in determining food resources. The study was conducted from 22 September 2008- 21 September 2009 in the Avicennia marina habitat that stands in Hara Protected Area (HPA) and Rhizophora mucronata habitat that stands in International Wetland of Gaz and Hara Rivers Delta (GHRD). Bird observations were conducted using a point count method and results were categorized into the types of birds including wading birds, seabirds and waterfowls. A total of 76074 waterbird observations, representing 62 species from 15 families and 5 orders, were recorded in two sites. Based on the type of bird category, a total of 57373 (43 spp.), 18681 (17 spp.), 20 (2 spp.) observations were recorded in the categories of waders, seabirds and waterfowls respectively. From these observations, a total of 59387 waterbird observations, representing 56 species were recorded at HPA, while 16687 observations, belonging to 54 species were recorded at GHRD. Moreover, based on category of bird a total of 44078 waders, 15297 seabirds and 12 waterfowls were recorded at HPA and 13295 waders, 3384 seabirds and 8 sightings of waterfowls at GHRD. Forty eight species of waterbird (15 families) were common in both habitats. Eight species exclusively used HPA while six species occurred only at GHRD. The Crab Plover (Pluvialis squatarola) and Eurasian Curlew (Numenius arquata) were the dominant species at HPA and GHRD, respectively. The abundance of all waterbirds for two habitats was highly significant (P< 0.001). The mean values abundance of the waterbirds by seasons was higher at HPA than GHRD mangrove forest (3711±427 observations vs. 1283±209 observations). This study indicated that there were highly significant differences among the all surface water variables including temperature, pH, EC, TSS and salinity (p<0.01), excluding DO (p>0.05) with habitat. The soil parameters also showed significant difference between two habitats for available potassium, organic carbon, percentage of clay and silt at depth of 0-20 cm, and organic carbon, pH, EC and percentage of sand and silt at depth of 20-40 cm (p<0.05). In general, R. mucronata occurs with higher density, tree height and canopy than A. marina in the coast of Hormozgan province (p>0.05). While diameter at breast height and crown spread for A. marina were higher than R. mucronata. Furthermore, there was a significant difference in number of gastropods between the two types of mangroves (t=1.34, p<0.05), but there was no significant difference in number of mudskipper between the mangroves (t=2.041, p<0.05). A strong positive response was found between the environmental variables and abundance of waterbirds, using redundancy analysis. However, soil parameters did not highly affect the abundance of waterbird species, but they were important in growth of mangroves and habitat of gastropods. As a conclusion, results of this study supported the hypothesis that microenvironment and micro-habitat factors could affect the composition, abundance, density and diversity of the waterbirds especially waders across the two types of mangrove vegetation. Therefore, changes in the environmental variables are the key factors that influence the waterbird response. Thus the waterbird populations can be used as a key tool for monitoring the status of mangrove habitats and environmental changes.